Analysis of the Effecting Factors on Regional Real Income in Bone Regency - Ramli, Anwar (Archives of Business Research, 2016)
Regional real income is an important aspect in increasing the economic prosperity of Bone Regency. The aims of this study were to determine: (i) regional tax, (ii) regional retribution, (iii) self-governing regional wealth yield, and (iv) miscellaneous official regional real income that affected regional real income of Bone Regency. The study was analyzed by using method of time series. Results of F-value for regional tax, regional retribution, self-governing regional wealth yield, and miscellaneous official regional real income had significant effect on regional real income of Bone regency. Results of t-test revealed that: (i) regional tax variable was not statistically significant affecting regional real income; (ii) regional retribution variable was not statistically significant affecting regional real income; (iii) self-governing regional wealth yield variable was not statistically significant affecting regional real income and; (v) miscellaneous official real regional income variable was not prove significantly affecting regional real income of Bone regency, respectively.